2015
DOI: 10.1007/s12598-015-0615-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of boron in TiAl alloy development: a review

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Based on this understanding, the traces labeled by the black arrows are actually the previous grain boundaries of a high temperature α grain. After careful observation of the traces in Figure 2, one can realize that the grain sizes of the α grains during 1340 • C heat treatment are similar, i.e., approximately 200-300 µm in both images, which is in accordance with other reports [31,32]. This finding can further lead to the conclusion that the growth rate of α grains may decrease with the increase of time.…”
Section: Effects Of Heat Treatment Parameters On the Massive Transforsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on this understanding, the traces labeled by the black arrows are actually the previous grain boundaries of a high temperature α grain. After careful observation of the traces in Figure 2, one can realize that the grain sizes of the α grains during 1340 • C heat treatment are similar, i.e., approximately 200-300 µm in both images, which is in accordance with other reports [31,32]. This finding can further lead to the conclusion that the growth rate of α grains may decrease with the increase of time.…”
Section: Effects Of Heat Treatment Parameters On the Massive Transforsupporting
confidence: 87%
“…The black arrows in Figure 2 indicate the locations of borides. As reviewed by Hu et al, the borides can act as barriers during the growth of α phase at high temperatures [31]. Based on this understanding, the traces labeled by the black arrows are actually the previous grain boundaries of a high temperature α grain.…”
Section: Effects Of Heat Treatment Parameters On the Massive Transformentioning
confidence: 90%
“…Hu et al. found that the borides can be used as the heterogeneous nucleation during the β→α transition and refined lamellar colonies produced in the boron‐added alloys . Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…discovered that the more the amount of boron added, the less the content of the phase transition texture . However, it should be pointed out that the beneficial effects were suppressed as cracks appear on large titanium borides . Besides, the cooling rate during β→α transition takes an important place in determining the microstructure characteristics of α phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation